Impact of Lung Function Decline on Mortality in Lung Transplant Recipients: Long-Term Results From the L-CsA-i Study for the Prevention of Bronchiolitis Obliterans Syndrome - Kneidinger, Nikolaus; Ghiani, Alessandro; Milger, Katrin; Monforte, Víctor; Knoop, Christiane; Jaksch, Peter; Parmar, Jasvir; Ussetti, Piedad; Solé, Amparo; Müller-Quernheim, Joachim; Voelp, Andreas; Behr, Juergen; et al. (Frontiers in Medicine, 2022)
BACKGORUND: Chronic lung allograft dysfunction (CLAD) is defined by a progressive loss of FEV1 and is associated with premature mortality. The aim of this study was to investigate the direct association between FEV1 decline and risk of mortality in patients after lung transplantation (LTx). METHODS: 10-year follow up data from lung transplant recipients participating in randomized placebo-controlled clinical trial investigating the role of liposomal Cyclosporine A for inhalation (L-CsA-i) in the prevention of bronchiolitis obliterans syndrome (NCT01334892) was used. The association between the course of FEV1 over time and the risk of mortality was assessed using joint modeling and Cox regression analysis. RESULTS: A total of 130 patients were included. Predictors of FEV1 decline were a higher absolute FEV1 at baseline and male sex. The joint model analysis indicated a significant association of change of FEV1 and risk of mortality (p<0.001), with a predicted 3.4% increase in mortality risk for each 1% decline in FEV1. Significant predictors of a progressive phenotype were single LTx and treatment with placebo (as opposed to L-CsA-i). At the end of follow-up, 82 patients (63.1%) were still alive. Cox regression analyses for mortality identified only single LTx as a predictor of higher risk. CONCLUSION: Based on our observation of a close association between FEV1 and mortality over aperiod of 10 years we suggest FEV1 as a valid predictor of mortality and a suitable surrogate endpoint in the investigation of early interventions.